From Terrorism to Flooding: How Vulnerable is Your City?. Issue 1 (3rd February 2021) - Piegorsch, Walter W.; McCaster, Rachel R.; Cutter, Susan L.
Abstract: Walter W. Piegorsch, Rachel R. McCaster and Susan L. Cutter explain how the tools of data science can help quantify the risks and vulnerabilities to hazards in the places where we live and work